2016
DOI: 10.1039/c6pp00307a
|View full text |Cite
|
Sign up to set email alerts
|

The unquenched triplet excited state of the fluorescent OFF/ON Bodipy-derived molecular probe based on photo-induced electron transfer

Abstract: Fluorescent molecular probes based on photo-induced electron transfer (PET) are well-known for which fluorescence is efficiently tuned OFF/ON by a PET process. Now we demonstrate that the triplet excited state of the probes is unable to be quenched by PET, which is in stark contrast to the singlet excited state (fluorescence). This conclusion was proved by the preparation of a fluorescent molecular probe BDP-DPA, which shows enhanced fluorescence upon addition of a Zn(ii) salt. With fluorescence spectroscopy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 38 publications
1
24
0
Order By: Relevance
“…According to previous reports, the preparation of the triad from meso ‐chloro‐BODIPY should be a rather straightforward substitution reaction at the 8‐chloromethyl site (see DBT′, expected structure, Scheme ) . However, after the reaction, the 1 H NMR spectrum of the product indicated that the four methyl groups on the BODIPY chromophore are inequivalent (see Figures S3 and S4 in the Supporting Information for the spectrum).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…According to previous reports, the preparation of the triad from meso ‐chloro‐BODIPY should be a rather straightforward substitution reaction at the 8‐chloromethyl site (see DBT′, expected structure, Scheme ) . However, after the reaction, the 1 H NMR spectrum of the product indicated that the four methyl groups on the BODIPY chromophore are inequivalent (see Figures S3 and S4 in the Supporting Information for the spectrum).…”
Section: Resultsmentioning
confidence: 83%
“…However, after the reaction, the 1 H NMR spectrum of the product indicated that the four methyl groups on the BODIPY chromophore are inequivalent (see Figures S3 and S4 in the Supporting Information for the spectrum). Single‐crystal XRD diffraction gave the molecular structure, which is drastically different to the expected “normal” molecular structure . Indeed, following single‐crystal XRD and 1 H NMR analyses, the molecular structure was unambiguously assigned to DBT, not the initially expected DBT′ (Scheme ).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The thermodynamic feasibility of SBCT was also estimated employing the Rehm–Weller analysis, which further confirmed the occurrence of SBCT in bis(dipyrrin) complexes under study (Table 2). [41, 42] …”
Section: Resultsmentioning
confidence: 99%
“…[30] The thermodynamic feasibility of SBCT was also estimated employing the Rehm-Weller analysis, which further confirmed the occurrence of SBCT in bis(dipyrrin) complexes under study (Table 2). [41,42] Femtosecond/nanosecond transient absorption spectra: symmetry charge transfer and intersystem crossing…”
Section: Steady State Uv/vis Absorption and Fluorescencespectramentioning
confidence: 99%